2012
DOI: 10.1093/europace/eus154
|View full text |Cite
|
Sign up to set email alerts
|

The relation between age, sex, comorbidity, and pharmacotherapy and the risk of syncope: a Danish nationwide study

Abstract: In a nationwide cohort of patients hospitalized for first syncope we found significant association between cardiovascular comorbidity and pharmacotherapy and the risk of syncope. The occurrence of syncope displayed an age distribution with important gender-specific differences and higher incidence rates than previously reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(63 citation statements)
references
References 24 publications
2
58
2
1
Order By: Relevance
“…33,34 Patients with syncope are characterized by greater burden of comorbidity and increased exposure to a greater number of medications. 2,32 In keeping with this, we noted that 1 in 5 of the working age individuals with syncope was on health-related Figure 3. Termination of employment among people with syncope.…”
Section: Termination Of Employment In the Syncope Populationsupporting
confidence: 65%
“…33,34 Patients with syncope are characterized by greater burden of comorbidity and increased exposure to a greater number of medications. 2,32 In keeping with this, we noted that 1 in 5 of the working age individuals with syncope was on health-related Figure 3. Termination of employment among people with syncope.…”
Section: Termination Of Employment In the Syncope Populationsupporting
confidence: 65%
“…In a Danish study, the risk of syncope in patients with cardiovascular disease was significantly higher in younger age groups,24 while Sandhu et al10 found that advancing age was a risk factor for all‐cause 30‐day readmissions. However, the latter study included hospitalizations for syncope/collapse as either a primary or secondary diagnosis and the outcome was only adjusted for sex and Charlson Comorbidity Index.…”
Section: Discussionmentioning
confidence: 98%
“…9,10 The lifetime cumulative incidence of syncope is ≥35%, with peak prevalence of the first episode between ages 10-35. 11 The incidence increases with age, especially after 70 years, 9,10 and is bimodal with peaks at 20 and 80 years.…”
Section: Epidemiologymentioning
confidence: 99%